2020
DOI: 10.1038/s41467-020-14370-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Eigen-like hydrated protons at negatively charged interfaces

Abstract: Despite the importance of the hydrogen ion in a wide range of biological, chemical, and physical processes, its molecular structure in solution remains lively debated. Progress has been primarily hampered by the extreme diffuse nature of the vibrational signatures of hydrated protons in bulk solution. Using the inherently surface-specific vibrational sum frequency spectroscopy technique, we show that at selected negatively charged interfaces, a resolved spectral feature directly linked to the H 3 O + core in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
(101 reference statements)
3
17
0
Order By: Relevance
“…This effect arises from the strong co‐adsorption of hydronium to the interface with its chloride counter ion with increasing acid concentration, which creates a minimal amount of water solvation in a 2D interfacial network with a reduced hydrogen‐bonding capacity [69] . In fact only recently has evidence of the hydration structure of protons at an interface been observed, where Eigen‐like hydrated protons (H 9 O 4 + ) were identified near negatively charged monolayers at biologically relevant pH, [70] similar to the observations made here.…”
Section: Discussionsupporting
confidence: 85%
“…This effect arises from the strong co‐adsorption of hydronium to the interface with its chloride counter ion with increasing acid concentration, which creates a minimal amount of water solvation in a 2D interfacial network with a reduced hydrogen‐bonding capacity [69] . In fact only recently has evidence of the hydration structure of protons at an interface been observed, where Eigen‐like hydrated protons (H 9 O 4 + ) were identified near negatively charged monolayers at biologically relevant pH, [70] similar to the observations made here.…”
Section: Discussionsupporting
confidence: 85%
“…All energetics reported in this study were calculated under U = −1.0 V SHE and pH = 6.8 conditions. The Eigen complex, where a proton is solvated by four explicit water molecules, was used as the proton source to locate the transition state of hydrogenation by a proton–electron pair . A previous theoretical study demonstrated that the results obtained from this Eigen model are similar to those obtained by using a water bilayer model .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The structure and dynamics of aqueous interfaces is of high relevance for many different scientific fields. [1][2][3][4][5][6][7][8][9] Many important chemical and biological processes take place at aqueous interfaces, like for instance molecular recognition at bio-membranes, protein folding, and energy conversion and storage. [10][11][12][13][14][15] The structural properties of the neat water/air interface 16,17 and charged aqueous interfaces have been extensively studied with vibrational sum-frequency generation spectroscopy (VSFG) in the frequency region of the water OH stretch vibrations.…”
Section: Introductionmentioning
confidence: 99%